Applied NMR Spectroscopy for Chemists and Life Scientists - Zerbe, Oliver Jurt, Simon (Wiley-VCH, 2014)
From complex structure elucidation to biomolecular interactions - this applicationoriented textbook covers both theory and practice of modern NMR applications. Part one sets the stage with a general description of NMR introducing important parameters such as the chemical shift and scalar or dipolar couplings. Part two describes the theory behind NMR, providing a profound understanding of the involved spin physics, deliberately kept shorter than in other NMR textbooks, and without a rigorous mathematical treatment of all the physico-chemical computations